Analysis of Soil Biological Conditions in Organic and Inorganic Agriculture Areas in Tanah Datar Regency - Nasution, Ade Fitriadi; Adelina Harahap, Rasmita (Talenta Publisher, 2021)
Enzyme activity due to soil microbial activity is an important event in knowing the status of microbial biomass and as an indicator of the occurrence of nutrient cycling. This activity is not just a chemical event, but rather a complex biological process related to the interaction of life interests between organism. The activities of each soil microbial group further emphasize its diversity status, and have an impact on various bioprocess events that allow the degradation and synthesis of soil organic matter. Respiration events are a description of the acceleration of bioprocesses carried out by soil microbial biomass. The implementation of an enzymatic process can reflect an integrated chemical process, physics and mineralization that occurs in the soil as a result of microbial activity, in maintaining and realizing the resilience of its ecosystem. This research is a survey method and soil sampling (purposive sampling) followed by soil testing in the laboratory with the following stages: (a) analysis of experimental soil samples at the Soil Biology Laboratory, Soil Research Institute, Bogor, (b) interview. Analysis of organic and organic soil nitrogenase activity in Jorong Carano Batirai and Jorong Aie Angek, Tanah Datar Regency obtained a total of 4 samples. Indicates the presence of nitrogenase activity, namely NOI, NAI, NOII and NAII. The highest nitrogenase activity based on ARA was in the NOII sample and the lowest was in the NAI sample. Land management affects urease activity, urease is an enzyme that is sensitive to various levels of land management. Higher urease activity with organic use, because the level of land management is less intensive and receives little inorganic fertilizer or pesticide. Keywords : soil enzyme activity, soil biological fertility